Asymptotic behavior of a stochastic population model with Allee effect by Lévy jumps. (May 2017) - Zhang, Qiumei; Jiang, Daqing; Zhao, Yanan; O'Regan, Donal
Abstract: This paper presents the analysis of asymptotic behavior of a stochastic population model with Allee effect by Lévy jumps. The criteria of the asymptotic behavior for this perturbed model is given via using Lyapunov analysis methods. Numerical simulations for a set of parameter values are presented to illustrate the analytical findings.